(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objectives: To evaluate the perinatal outcomes of thoracoamniotic shunting for fetal pleural effusion at Hanoi Obstetrics and Gynecology Hospital. Materials and Methods: A prospective descriptive study was conducted on 11 cases diagnosed with fetal pleural effusion indicated for thoracoamniotic shunting at Hanoi Obstetrics and Gynecology Hospital from May 2025 to March 2026. Results: The mean gestational age at birth was 34.58 ± 1.71 weeks, with no cases of full-term delivery. 100% of cases were delivered via Cesarean section. The mean birth weight was 2486 ± 427.84 grams. Infants weighing over 2500 grams accounted for 54.5%. The average Apgar scores at 1 and 5 minutes were 7 ± 1.18 and 8.09 ± 0.94, respectively. Postnatal pleural effusion recurrence was recorded in 27.3% of cases. No mortality was recorded within the first 24 hours after birth. At 28 days postnatal, there were 4 deaths (36.36%). Conclusion: Thoracoamniotic shunting helps prolong pregnancy and improves early neonatal status in fetuses with pleural effusion. The survival rate in the first 24 hours is high. However, the risk of postnatal mortality remains, primarily related to recurrent pleural effusion and respiratory distress.